PERBANDINGAN PENERAPAN TEKNIK PENILAIAN KINERJA DAN TEKNIK PENILAIAN TERTULIS TIPE URAIAN TERBATAS DALAM PEMBELAJARAN MATEMATIKA DITINJAU DARI HASIL BELAJAR SISWA - elmayanti Badriani; Edi prio baskoro; budi manfaat (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2015)
Selection of assessment Technique in study evaluation can influence the result learn the student. Specially in mathematics study, in evaluation of study of assessment technique not only fetched up all standing at written it just by assessment technique but a lot of choice of assessment technique which can awaken the study atmosphere become creative and active. In this case evaluate the study require to be improve repaired to by utilize to improve the result learn the student. Therefore, this research try to compare the technique of performance assessment with the assessment technique written in mathematics study of at discussion fundamental mark with lines and angle corner evaluated from result learn student. This study aims to determine whether there are difference to the results of students mathematics learning among students in group learning by using the techniques of evaluation and performance assessment of students in group learning by using valuation techniques evaluation written description of the type limited to the subject line and angle in class VII SMP 1 Cilimus District Brass. This study is a quasi-experimental research. Affordable population in this study were students of second grade at SMPN 1 Cilimus Academic Year 2014/2015. Samples were selected using random cluster sampling technique, was elected class VII.7 the number of students 36 people and VII.8 by the number of students 37 people as the sample. The research instrument used in the form of tests. The average math student learning outcomes in the experimental group I in both categories, shown by the average number of 84,93 with a standard deviation of 5,98 and the average math student learning outcomes in the experimental group II in both categories, indicated by the numbers an average of 81,39 with a standard deviation of 6,08. Hypothesis test results conclude that there are difference to the results of students' mathematics learning among students in group learning by using the techniques of evaluation and performance assessment of students in group learning by using valuation techniques evaluation written description of the type limited to the subject line and angle in class VII SMPN 1 Cilimus District Brass at significance level of 5%.Keywords: Comparison, Student Learning Outcomes, Performance Assessment, Written Assessment Limited Description Type